Prevalence of and Risk Factors for Poor Sleep During Different Trimesters of Pregnancy Among Women in China: A Cross-Sectional Study - Zhang, Huishan (Nat Sci Sleep, 2021)
BACKGROUND: The management of poor sleep during pregnancy is important for maternal and foetal health. The aim of the present study was to investigate the prevalence of poor sleep quality and risk factors for poor sleep during different trimesters of pregnancy for better management of sleep during pregnancy. METHODS: A cross-sectional study was conducted among pregnant women in Foshan Women’s and Children’s Hospital. In total, 2281 pregnant women were analysed, and the Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. Cluster logistic regression was used to analyse the risk factors for poor sleep among all participants, and logistic regression models were built to identify potential risk factors for poor sleep quality in different trimesters of pregnancy. RESULTS: Over half of the participants reported poor sleep quality (51.8%). The rate of poor sleep was lowest in the second trimester. Women who were unmarried had >12 years of education, exercised <3 days/week, were in the third trimester, had a high level of nausea and vomiting during pregnancy (NVP) and had a history of infertility had a higher risk of poor sleep. Pregnancy-related factors contributed most to poor sleep. In the first trimester, the main risk factors for poor sleep were a history of infertility and a high level of NVP. In the second trimester, only a high level of NVP was a risk factor for poor sleep. In the last trimester, the risk factors for poor sleep were more education years, exercise <3 days/week and high levels of NVP. CONCLUSION: The prevalence and risk factors for poor sleep were different in different trimesters. Clinicians should screen and address poor sleep prior to the first and, especially, the third trimester of pregnancy. Management of poor sleep should be consistent throughout pregnancy and be adjusted in different trimesters.